Drive and Violence : Metamorphoses of Sexual Repression Between Patriarchy and Progressivism - Gagliardi, Simone (Quaderni di Psicologia Clinica, 2025)
The central thesis of this article is that it is impossible to establish a normative order capable of pacifying human sexuality. Social institutions can and must regulate, sanction, and shape it, but they cannot resolve the inherent violence that inhabits it. Any discourse that seeks to discipline sexuality into a harmonious and peaceful form inevitably produces mechanisms of repression. As Freud teaches, the repressed always returns, condemning the repressing discourse to some form of collapse. This paper develops this thesis starting from Georges Bataille’s reflections, linking them to psychoanalytic, neuroscientific, and evolutionary references, and shows how different social discourses — from patriarchy to contemporary progressive movements —continue to generate forms of repression around sexuality. Finally, two brief clinical cases illustrate how these dynamics can be observed in psychoanalytic practice.